2012
DOI: 10.3892/br.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

Semen Ziziphi Spinosae and Fructus Gardeniae extracts synergistically improve learning and memory of a mouse model

Abstract: Abstract. Semen Ziziphi Spinosae (SZS) and Fructus Gardeniae (FG) are two herbs commonly used in traditional Chinese medicine. Previous studies have suggested that Fructus Gardeniae as well as Semen Ziziphi Spinosae are able to regulate the function of the central nervous system. However, their effect on learning and memory has yet to be elucidated. In this study, we examined the effect of SZS and FG on the learning and memory of mice using the methods of step-through and -down passive avoidance tasks and Morr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Z. spinosae Semen is the mature seed of sour jujube, and is used as a sedative agent in TCM [21,22,23]. Z. spinosae Semen could improve learning and memory of mice [24]. It has been reported to have an antidepressant effect in a rat depressive model [25].…”
Section: Introductionmentioning
confidence: 99%
“…Z. spinosae Semen is the mature seed of sour jujube, and is used as a sedative agent in TCM [21,22,23]. Z. spinosae Semen could improve learning and memory of mice [24]. It has been reported to have an antidepressant effect in a rat depressive model [25].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 10 ] In order to treat these disorders (including dementia, amnesia and Alzheimer's disease), it is meaningful to exploit natural nutraceutical with the effect of ameliorating learning and memory. Recently, it is found that ZSS oil exhibits certain improving effects of learning and memory in mice,[ 11 ] which manifested the great potential of ZSS as a dietary supplement for treatment of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We recently examined the effects of Ziziphi Spinosae and Fructus Gardeniae, two herbs commonly used in traditional Chinese medicine, on the learning and memory of mice in a Morris water maze test (15). It was observed that the compound extracts of Ziziphi Spinosae and Fructus Gardeniae had a synergistic effect on the learning and memory of mice (15).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the compound extracts of Ziziphi Spinosae and Fructus Gardeniae had a synergistic effect on the learning and memory of mice (15). In the current study, the effect of jujube on the learning and memory of ovariectomized rats was investigated using the Morris water maze test.…”
Section: Introductionmentioning
confidence: 99%